Impact of thromboplastin reagents on monitoring INR in a patient with triple-positive antiphospholipid syndrome: a case report - Lóránt Varju; Lóránt Varju; Zsuzsa Bagoly; Zsuzsa Bagoly; Éva Ajzner; Rita Orbán-Kálmándi; Rita Orbán-Kálmándi; Anna Zsófia Kádár; Anna Zsófia Kádár; Judit Nevelős; Péter Ilonczai (Frontiers in Immunology)
IntroductionAntiphospholipid syndrome (APS) is an autoimmune disease characterized by a hypercoagulable state and recurrent thromboembolism (TE). Patients with triple-positive antiphospholipid antibodies (APAs) are at the highest risk of TE. As standard treatment for these patients, oral anticoagulation therapy (OAT) with vitamin K antagonists (VKAs) is widely used, but inaccurate International Normalized Ratio (INR) measurement due to APA interference can complicate monitoring.CaseHere we report the case of a 19-year-old male patient, with a history of submassive pulmonary embolism at the age of 13. Thrombophilia investigations confirmed type II antithrombin deficiency (Budapest 3 heterozygous) combined with triple-positive APS. He received sustained VKA (warfarin) therapy, but his INR values showed strikingly different results when monitored in two different laboratories (INR 3–4 vs. INR >8 on multiple occasions). Therefore, we aimed to investigate the impact of different thromboplastin reagents on INR values in this triple-positive APS patient receiving VKA therapy. INR measurements were performed using animal-derived (rabbit brain-derived) and recombinant thromboplastins. The effect of purified patient IgG concentrates was examined on INR values using antiphospholipid antibody-negative plasma mixtures. Chromogenic FXa activity (CFXa) was also measured to assess the true anticoagulant effect of VKA.ConclusionsINR values measured using recombinant thromboplastin reagent were consistently higher and less reliable in high APA-titer conditions compared to rabbit brain-derived reagent. CFXa results were more consistent with INR values obtained using rabbit brain-derived thromboplastin. Rabbit brain-derived thromboplastin, less sensitive to APA interference, provided reliable INR monitoring for this high-risk patient. We recommend choosing thromboplastin reagents without interference to APAs, to optimize OAT monitoring in similar cases of patients with high APA-titers.